Community Empowerment Strategy in Management of Swallow's Nest Cultivation to Increase Regional Original Income In Kotabaru District - Muhammad Risaad; Riduansah Syafari; Andi Tenri Sompa; Setia Budhi; Ahmad Yunani (Wadah Inovasi Indonesia, 2021)
Community empowerment through swallow nest cultivation is one of the efforts of the Kotabaru Regency Government to increase local revenue (PAD). This study aims to describe a strategy for community empowerment in the management of swallow nest cultivation and the supporting and inhibiting factors for implementing the strategy. This research uses the descriptive qualitative method. They were collecting data using in-depth interviews, observation, and document review. The results showed that Kotabaru Regency's Original Regional Revenue (PAD) from community empowerment through swallow nest cultivation was insignificant. The reason is that there are still many weaknesses in the implemented community empowerment strategies. Strategies applied based on SWOT analysis, namely: a) Application of SO (Strength – Opportunities) strategy, is 1. Business assistance. 2 . Protection of business objects.; b) The implementation of the WO (Weakness – Opportunities) strategy is 1. Mapping social potential participatory in developing swallow nest cultivation business; 2. Community organizing and facilitation of sustainable program setting; 3. Capacity building of the community. c) The implementation of ST (Strength – Threats) strategy is 1 . Regulatory determination; 2. Socialization of empowerment. d The application of the WT (Weaknesses – Threats) strategy is 1. Input (capital support, infrastructure, and facilities). 2. Market access for swallow nests. 3. Development of cooperation/network.